Joint analysis of national eco-efficiency, eco-innovation and SDGS in Europe: DEA approach - Łącka, Irena; Brzezicki, Łukasz (Technological and Economic Development of Economy, 2022)
The growing complexity and intertwining of different socio-economic issues both in individual countries and internationally mean that single-theme analyses do not consider all the relationships and thus have cognitive limitations. Therefore, studies that combine several research areas are increasingly common in the literature to clarify the connections and relationships. In this study, considering the sequential nature of the stages, a combined analysis of eco-efficiency, eco-innovation, and Sustainable Development Goals (SDGs) was performed. The analysis was carried out for 27 European Union countries in 2017–2019. Dynamic Network SBM and Dynamic Divisional Malmquist Index were used for the study. The research results show that the EU countries achieve relatively higher efficiency results in eco-innovation and SDG than ecoefficiency. The average overall efficiency level for all EU countries was only 0.63. The change in productivity was influenced by both the frontier shift and catch-up effect, but only with regard to eco-efficiency and eco-innovation. At the same time, the frontier-shift effect did not affect the change in SDG productivity.First published online 19 October 2022